Pre-Service Teachers’ Experiences in Developing Digital Learning Designs using ADDIE Model Amid COVID-19 Pandemic - Asep Nuryadin; Dindin Abdul Muiz Lidinillah; Muhammad Rijal Wahid Muharram (Jurnal Basicedu, 2021)
This study aims to discover pre-service teachers’ experiences in developing digital learning designs during the COVID-19 pandemic. It is expected that the findings of this study can help lecturers, university students, higher education institutions, and other relevant stakeholders in preparing the implementation of learning amid a global pandemic or other relevant crises, especially related to conducting the development of a particular design or product using ADDIE model. The method used in this study was a case study with a descriptive approach. Research subjects or participants involved in this study were 41 pre-service teachers who took a unit named “Desain Sistem Pembelajaran Digital or Digital Learning System Design” offered in the sixth semester in Bachelor of Elementary School Teacher Education Study Program, UPI Tasikmalaya Campus. This study results in several findings related to pre-service teachers’ experiences in developing digital learning designs using the ADDIE model amid the COVID-19 pandemic. In addition, this study also has discovered information regarding digital learning designs and digital learning materials/tools developed by the pre-service teachers.